2019
DOI: 10.21037/atm.2019.04.79
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine coating promotes early osteogenesis in 3D printing porous Ti6Al4V scaffolds

Abstract: Background: Titanium implants are widely used in orthopedic and dental for more than 30 years. Its stable physicochemical properties and mechanical strength are indeed appropriate for implantation. However, the Bioinertia oxidized layer and higher elastic modulus often lead to the early implantation failure. Methods: In this study, we proposed a simple design of porous structure to minimize the disparity between scaffold and natural bone tissue, and introduced a one-step reaction to form a polydopamine (PDA) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 63 publications
0
38
0
Order By: Relevance
“…Researchers further explored HA in the form of composites, with studies reporting improved bone ingrowth for HA doped with magnesium, 49 polydopamine, 45 silicon, 59 or strontium 59 compared to uncoated controls, though the silicon and strontium groups did not show the same improvement when compared to undoped HA coatings 59 . Aside from HA, polydopamine coatings, 48,52 titanium copper and titanium copper nitride films, 37 growth factor‐doped fibrin glue, 51 and strontium‐laden nanotube coatings 55 also showed success in increasing 3DP pTi bioactivity. Instead of coatings, one study by Li et al used surface heat treatments to induce material phase transformations, 53 reporting that samples treated at 950 and 1000°C were associated with higher rates of bone formation, thicker bone trabeculae, and greater push‐out loads 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers further explored HA in the form of composites, with studies reporting improved bone ingrowth for HA doped with magnesium, 49 polydopamine, 45 silicon, 59 or strontium 59 compared to uncoated controls, though the silicon and strontium groups did not show the same improvement when compared to undoped HA coatings 59 . Aside from HA, polydopamine coatings, 48,52 titanium copper and titanium copper nitride films, 37 growth factor‐doped fibrin glue, 51 and strontium‐laden nanotube coatings 55 also showed success in increasing 3DP pTi bioactivity. Instead of coatings, one study by Li et al used surface heat treatments to induce material phase transformations, 53 reporting that samples treated at 950 and 1000°C were associated with higher rates of bone formation, thicker bone trabeculae, and greater push‐out loads 53 .…”
Section: Discussionmentioning
confidence: 99%
“…For bone regeneration, a scaffold should be biodegradable and biocompatible, as well as having osteoconductive, osteoinductive, and osteogenic properties ( 4 ). In addition, it is desirable that it provides an appropriate exchange of nutrients, promotes vascularization and bone ingrowth, and has a pore size ranging from 100 to 500 µm ( 5 ).…”
Section: Degradable Biomaterials For Bone Regeneration In Orthopedicsmentioning
confidence: 99%
“…[158] Although 100 μm is acceptable, a pore size of at least 300 μm is suggested for new bone formation, [159] and the pore size of 400 μm is optimal for vascularization during osteogenesis. [160] A specialized study showed that scaffold pore sizes larger than 390 μm with upper limit of 590 μm are more able to enhance bone tissue formation. [161] The strut thickness and microporosity can also affect the cell penetration and tissue ingrowth in the scaffold.…”
Section: Correlation Between Pore Characteristics and Scaffold Propertiesmentioning
confidence: 99%